2019
DOI: 10.1002/dc.24375
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follicular neoplasm with papillary like nuclear features: A comprehensive analysis with a diagnostic algorithm

Abstract: Background Noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) lacks the carcinoma label, avoiding aggressive therapy, physiological, social and financial impact of cancer diagnosis. Unfortunately, the preoperative diagnosis is still a challenge. Varied incidence of NIFTP has been document with limited data on preoperative cytological, radiological characteristics and the impact on risk of malignancy in each category of the Bethesda system of reporting thyroid cytopathology. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…Gland Surg 2021;10(1):307-318 | http://dx.doi.org/10.21037/gs-20-612 rare with percentage ranging from 2.5% to 7.5% according to our data aggregation (12,13,17,18,20,21). The aggregated data also showed the echogenicity of NIFTP was unspecific with similar distribution between hypoecho/marked hypoecho and isoechoic/hyperecho (105/241, 43.5% vs. 136/241, 56.4%).…”
Section: Rightmentioning
confidence: 57%
See 2 more Smart Citations
“…Gland Surg 2021;10(1):307-318 | http://dx.doi.org/10.21037/gs-20-612 rare with percentage ranging from 2.5% to 7.5% according to our data aggregation (12,13,17,18,20,21). The aggregated data also showed the echogenicity of NIFTP was unspecific with similar distribution between hypoecho/marked hypoecho and isoechoic/hyperecho (105/241, 43.5% vs. 136/241, 56.4%).…”
Section: Rightmentioning
confidence: 57%
“…Type-B was identified more frequently in macrogroup of our cases, which means that it may be associated with NIFTP in larger size. The pooling data showed that partially cystic change occupies 20% among all types of component, therefore, this US subset of NIFTP should not be ignored (12,13,17,18,20,21). As for type-C, it contains NIFTP showing other suspected features, including irregular margin, nonparallel shape, and calcifications.…”
Section: Rightmentioning
confidence: 98%
See 1 more Smart Citation
“…As Seethala et al (50) noticed, evaluating nuclear features of PTC as a "core diagnostic feature" of NIFTP should compare with the adjacent healthy thyroid tissue, which is not possible for cytology samples. Thus, the creation of a diagnostic algorithm to predict NIFTP by fine-needle aspiration biopsy (FNAB) has been proposed by cytopathologists (51). However, most studies supporting this proposal suffered from insufficient reproducibility.…”
Section: Cytologymentioning
confidence: 99%
“…Several studies have compared NIFTP and FVPTC (non-NIFTP) from various aspects including ultrasonic and pathological findings [4][5][6][7][8][9][10][11][12][13][14][15][16]. On ultrasound, the rate of findings suspected of malignancy in NIFTP was reported to be lower than that in non-NIFTP [10,11,[13][14][15]. In contrast, Hirokawa et al showed that on cytology, 75.7% of NIFTP cases were reported as suspicious for malignancy or malignant [4].…”
mentioning
confidence: 99%